Urinary outcomes of minimally invasive treatments for prostate cancer: a systematic review by young academic urologists’ urotechnology working group - Taratkin, Mark; Androsov, Alexander; Morozov, Andrey; Azilgareeva, Camilla; Rivas, Juan Gomez; Puliatti, Stefano; Checcucci, Enrico; Belenchon, Ines Rivero; Kowalewski, Karl-Friedrich; Rodler, Severin; Piazza, Pietro; Baekelandt, Loïc; et al. (Journal of endourology, 2025)
Introduction: Minimally invasive treatments (MITs) have emerged as viable treatment options for carefully selected patients with localized disease. Their major advantage is that MITs enable the preservation of nearby healthy prostate tissue and critical structures such as the urethral sphincter and neurovascular bundles without compromising oncologic outcomes. The aim of the current review is to describe the impact of different MITs for prostate cancer (PCa) on urinary continence. - Materials and Methods: A systematic literature search was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines. Inclusion criteria were as follows: all clinical trials conducted and related to the urinary outcomes (UO) of PCa MITs. Exclusion criteria were as follows: any reviews, articles, conference abstracts, articles whose subject fell outside the scope of this review, or any articles published more than 5 years ago. - Results: In the course of the last 5 years, a total of 114 articles on MITs of PCa have been published. Among them, only 36 dealt with the UO for MITs. Brachytherapy, cryoablation, and high-intensity focused ultrasound (HIFU) seem to be the most widely used technologies, whereas irreversible electroporation, focal brachytherapy, focal cryoablation, and multi-parametric magnetic resonance imaging-ultrasound-guided (mpMRI-US-guided) HIFU seem to be the safest techniques in terms of UO. - Conclusion: The use of MITs for treating PCa is a fast-growing option that can help preserve functional parameters and urinary continence close to their normal levels. It should be noted that although there are currently limited data available on all MITs for the treatment of PCa, the ones that have been extensively studied have shown promising results.